Random Dissemination Algorithm of Stete-Updating Message for Distributed Virtual Environments of P2P Architecture - Tao Li; Hua Hu; Haiyang Hu (Dianxin kexue)
With the aim at optimizing view consistency in P2P distributed virtual environments, a random broadcasting algorithm for distributing state-updating message among users was proposed. By considering the limited network bandwidth and communication delay, which may affect the users' sensing of the real-life experience and the real-time interaction for the participants, the method was given based on the pre-established random geometric graph to distribute the state-updating messages. The greedy routing algorithm can find the forwarding route and obtain the message-spreading time between the source and the destinations. By compared with several other algorithms, the experiment results show that the random broadcast algorithm can reduce the event rates of the time-space inconsistency and improve the system performance.